Compute the limit $$\lim_{n\to\infty} \left(\int_0^{\pi} \frac{\sin^2 n x}{\sin x} \ dx-\sum_{k=1}^n \frac{1}{k}\right)$$


Lemma: $\int_{0}^{\pi} e^{(2n+1)ix} dx = \frac{-2}{i}(2n+1)$.

Now let $t=e^{ix}$. We'll simplify the integrand: $$\frac{\sin^2(nx)}{\sin x} = (\frac{t^{n}-t^{-n}}{2i})^2 (\frac{t-t^{-1}}{2i})^{-1}$$ $$=\frac{i}{-2} \frac{t^{2n+1}+t^{1-2n}-2t}{t^2-1} = \frac{i}{-2} t \frac{t^{2n}-1}{t^2-1}(1-t^{-2n})$$ $$=\frac{i}{-2} \sum_{i=0}^{n-1} (t^{2i+1} - t^{2(i-n)+1})$$

Now, by applying the lemma, we find that the integral is $$\frac{i}{-2}\frac{-2}{i} \sum_{i=0}^{n-1} \frac{1}{2i+1} - \frac{1}{2(i-n)+1}=$$ $$=2 \sum_{i=0}^{n-1} \frac{1}{2i+1} =2(H_{2n}-\frac{1}{2}H_n)$$

So the limit in question is $\lim_{n \to \infty} 2(H_{2n}-\frac{1}{2}H_n) - H_{n} = \lim 2H_{2n}-2H_{n}$. Now we can either use $H_{n} \sim \log n + \gamma + O(n^{-1})$ or compare $H_{2n}-H_{n}$ to the integral $\int_{n}^{2n} \frac{dt}{t} = \ln 2$ to conclude that the limit is $\ln 4$.

  • $\begingroup$ By relating your last relation $$\lim_{n \to \infty} 2H_{2n}-2H_{n}$$ to Catalan-Botez identity and using the Taylor series of $\ln(x+1)$, the answer is clearly $2 \ln 2$. Thanks! (+1) $\endgroup$ – user 1591719 Dec 22 '12 at 17:27
  • $\begingroup$ @Chris'ssister There's also the integral approach, which is elaborated here: math.stackexchange.com/questions/155190/… $\endgroup$ – Ofir Dec 22 '12 at 17:31
  • $\begingroup$ yeah. That series is a well-known series and one may find lots of approaches. $\endgroup$ – user 1591719 Dec 22 '12 at 17:33

Let's suppose that $\ \displaystyle f(n):=\int_0^{\pi} \frac{\sin^2 n x}{\sin x} \ dx\ $ then : \begin{align} f(n+1)-f(n)&=\int_0^{\pi} \frac{\sin^2((n+1) x)-\sin^2(n x)}{\sin x} \ dx\\ &=\int_0^{\pi} \frac{\cos(2n x)-\cos(2(n+1) x)}{2\sin x} \ dx\\ &=\int_0^{\pi} \frac{\cos(2n x)(1-\cos(2x))+\sin(2nx)\sin(2x)}{2\sin x}dx\\ &=\int_0^{\pi} \frac{\cos(2n x)2\sin(x)^2)+\sin(2nx)2\sin(x)\cos(x)}{2\sin x} dx\\ &=\int_0^{\pi} \cos(2n x)\sin(x)+\sin(2nx)\cos(x)\;dx\\ &=\int_0^{\pi} \sin((2n+1) x)\;dx\\ &=\frac 2{2n+1} \\ \end{align}

So that your limit (as $\ (n+1)\to +\infty$) is the series : $$f(0)+\sum_{n=0}^\infty \left(\frac 2{2n+1}-\frac 1{n+1}\right)=2\sum_{n=0}^\infty \left(\frac 1{2n+1}-\frac 1{2n+2}\right)=2\,\log(1+1)=\log(4)$$ (using the expansion of $\;\log(1+x)\,$ at $\,x=1$)

  • 1
    $\begingroup$ thank you for your solution! (+1) $\endgroup$ – user 1591719 Dec 22 '12 at 17:22
  • $\begingroup$ Sorry for the errancies @Chris'ssister ... :-) $\endgroup$ – Raymond Manzoni Dec 22 '12 at 17:23
  • $\begingroup$ it's OK, and I'm always glad to receive your nice solutions! :) $\endgroup$ – user 1591719 Dec 22 '12 at 17:58
  • $\begingroup$ Your questions are welcome too @Chris'ssister ! $\endgroup$ – Raymond Manzoni Dec 22 '12 at 18:03

The point is that you can write $\sum_{k=1}^nsin(2k-1)x=\frac{cos(2nx)-1}{-2sinx}=\frac{sin^2(nx)}{sinx}$, so the integral is equal to $I=lim_{n\to\infty}\sum_{k=1}^n(\int_{0}^\pi(sin(2k-1)xdx-\frac{1}{k})=lim_{n\to\infty}\sum_{k=1}^n(\frac{2}{2k-1}-\frac{1}{k})$, then using $\sum_{k=1}^{n}\frac{1}{k}\sim log(n)+c$, $c$ is the Euler constant, so $I=lim_{n\to\infty}2[\sum_{k=1}^{2n}\frac{1}{k}-\sum_{k=1}^n\frac{1}{2k}]-\sum_{k=1}^n\frac{1}{k}=lim_{n\to\infty}(2log2n+2c-logn-c-logn-c)=2log2$.

  • $\begingroup$ I think that the answer is precisely log(4) since this is the answer of the series on the second line. A very good start! (+1) $\endgroup$ – user 1591719 Dec 22 '12 at 17:12
  • $\begingroup$ @Chris'ssister, thanks fixed. $\endgroup$ – ougao Dec 22 '12 at 18:10

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.